PENENTUAN KONDISI TRANSFORMATOR BERDASARKAN KANDUNGAN GAS TERLARUT MENGGUNAKAN METODE SEGITIGA DUVAL - Sismantara, I M.T.; Ariastina, W.G.; Amrita, A.A.N. (Jurnal SPEKTRUM, 2021)
Transformer failure may interrupt the electrical power delivery and causing a very high cost to the utility. In order to prevent failure in the transformer, continuous condition monitoring of a power transformer is necessary. Dissolved Gas Analysis (DGA) has been well known method for transformer condition monitoring. A number of techniques have been developed in order to assist engineers in interpreting the DGA test results. In this research, interpretation of DGA test results using Fuzzy Logic approach based on Duval's Triangle is introduced. The Fuzzy Logic was developed based on the mapping of the different areas within the Duval Triangle. The program validation was carried out by comparing the output program with the simulated fault condition. The analysis results indicated that the introduced approach has successfully determined the condition of the tested transformers. This approach, thus, would provide advantages over the conventional method in determining the transformer condition.